Ethical and political issues in healthcare choices in the pandemic era: the right to visit hospitalized - Alfano, Linda; Ciaccia, Romina; Ciliberti, Rosagemma (Medicina Historica, 2022)
Background The loneliness of hospitalized in healthcare facilities caused by the suspension of relations with their family members has been a characterizing aspect of the Covid 19 pandemic which still calls for delicate ethical reflections. Based on the implications that the interdictions and/or severe limitations on visits have had on the health of patients and their families, the paper aims to propose possible intervention strategies to reorganize places of care so that individual and collective good can be reconciled without ever compromising the principle of assistance centered on the person and his emotional references.Materials and Methods: An analysis of the literature of interest has been conducted also through electronic databases including PubMed, Scopus and Web of Science, integrated with data obtained from Web search engines.Results: To restrain the transmission of the COVID-19 infection in the hospital environment, the administrators of healthcare facilities have adopted highly restrictive measures which, by excluding the family circle from assisting the relative, have negatively affected the fragility and vulnerability of the same people who they wanted to protect and accompany them in the care pathways, neglecting possible alternative strategies that could have guaranteed both care and respect for the person and their emotions.Conclusions: The organizational models of hospital facilities should become flexible enough to give due prominence, even in emergency situations, to the transformative capabilities of staff in promoting the humanization and personalization of care.